RETRACTED: Models for improving the activities of enterprises - Otakuziyeva Zuhra; Iminova Nargizaxon; Khakimova Khulkar; Raximova Sevara (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001